Contribution of Linear Guest Chains to Relaxational Dynamics in Model Polymer Networks Probed by Time–Domain 1H NMR - Campise, Florencia (2015)
A series of end-linked polymer networks with varying contents of linear guest chains were investigated through swelling and time-domain NMR temperature dependent experiments. Taking advantage of the thermorheological simplicity of polydimethylsiloxane polymers, time–temperature superposition (TTS) was employed to expand the characteristic time scales of NMR exploration by about 2 orders of magnitude. A comparison between swelling data and tube model predictions reveals that NMR captures the dominant features of the equilibrium and dynamic properties of defects trapped in slightly cross-linked, entanglement-dominated polymer networks. As high-temperature experiments ensures a complete relaxation of the guest linear chains on the millisecond time scale of the NMR experiments, an accurate description of the network architecture can be provided. Contents of guest chains determined by NMR were found to agree within a 1 wt % accuracy with data of swelling experiments.